Structure and evolution of the lipase superfamily. - Yoshihide Hayashizaki; Lawrence Chan; Wen‐Hsiung Li (1992)
The lipase superfamily includes three vertebrate and three invertebrate (dipteran) proteins that show significant amino acid sequence similarity to one another. The vertebrate proteins are lipoprotein lipase (LPL), hepatic lipase (HL), and pancreatic lipase (PL). The dipteran proteins are Drosophila yolk proteins 1, 2, and 3. We review the relationships among these proteins that have been established according to gene structural relatedness and introduce our findings on the phylogenetic relationships, distance relationships, and evolutionary history of the lipase gene superfamily. Drosophila yolk proteins contain a 104 amino acid residue segment that is conserved with respect to the lipases. We have used the yolk proteins as an outgroup to root a phylogeny of the lipase family. Our phylogenetic reconstruction suggests that ancestral PL diverged earlier than HL and LPL, which share a more recent root. Human and bovine LPL are shown to be more closely related to murine LPL than to guinea pig LPL. A comparison of the distance (a measure of the number of substitutions between sequences) between mammalian and avian LPL reveals that guinea pig LPL has the largest distance from the other mammals. Human, rodent, and rabbit HL show marked divergence from one another, although they have similar relative rates of amino acid substitution when compared to human LPL as an outgroup. Human and porcine PL are not as divergent as human and rat HL, suggesting that PL is more conserved than HL. However, canine PL demonstrates an unusually rapid rate of substitution with respect to the other pancreatic lipases. The lipases share several structurally conserved features. One highly conserved sequence (Gly-Xaa-Ser-Xaa-Gly) contains the active site serine. This feature, which agrees with that found in serine esterases and proteases, is found within the entire spectrum of lipases, including the evolutionarily unrelated prokaryotic lipases. We review the location and possible activity of putative lipid binding domains. We have constructed a conservation index (CI) to display conserved structural features within the lipase gene family, a CI of 1.0 signifying perfect conservation. We have found a correlation between a high CI and the position of conserved functional structures. The putative lipid-binding domains of LPL and HL, the disulfide-bridging cysteine residues, catalytic residues, and N-linked glycosylation sites of LPL, HL, and PL all lie within regions having a CI of 0.8 or higher. A number of amino acid substitutions have been identified in familial hyperchylomicronemia which result in loss of LPL function.(ABSTRACT TRUNCATED AT 400 WORDS)